INEQUALITIES IN SUB-SAHARAN AFRICA: ANALYSIS OF THE REGIONAL SPECIFICITY ANDCASE STUDIES IN IVORY COAST AND MADAGASCAR. - (:unkn) unknown (My University, 2003)
The thesis presents an analysis of the determinants of the evolution of inequalities in the world, and in Sub-Saharan Africa in particular. It searches to identify not only the macroeconomic, but also the institutional, political and demographic factors that explain why Africa is the poorest and, probably from now on, the most unequal continent in the world. The thesis begins with an examination of the links between growth and income distribution. After a synthesis of the debate on the causes of development gaps, it proposes an econometric analysis of the explanatory factors of the structural level of inequalities and their evolution. The second part analyses the evolution of income distribution in Côte d’Ivoire and Madagascar at the microeconomic level, in order to identify the mechanisms that explain the impoverishment of an increasing part of the population, notably in urban areas, during periods of structural adjustment.
Keywords: African Research